Analisis Manajemen Nepotisme di Pondok Pesantren - Wahyudi Widodo (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
The analysis of nepotism management in Islamic boarding schools (pondok pesantren) aims to examine the impact of nepotistic practices on human resource management in these educational institutions. This study uses a literature review method, examining various sources related to pesantren management, nepotism, and human resource management principles. The literature review findings show that nepotism in Islamic boarding schools often occurs in the recruitment and promotion of teachers and staff. While this practice may preserve loyalty and traditional values, it can hinder innovation, professionalism, and the quality of education. The long-term effects of nepotism include weakened organizational efficiency and individual performance. Therefore, this study recommends the implementation of a competency-based and accountable management system, emphasizing transparency to improve the quality and effectiveness of human resource management in Islamic boarding schools.